Археологические данные о контактах населения Хазарскою каганата и дунайских болгар - Тотев, Б.; Пелевина, О. (Степи Европы в эпоху средневековья, 2009)
The problem of contacts of Danube Bulgaria with the population of the Khazar Qaganate since the time of the Saltov-Maiaki culture formation up to its last phase has more than once drawn the Russian and Bulgarian researchers attention. All of them adhered to the hypothesis that there were several waves (following the first one in the process of migration) of the groups of population from the Khazar Qaganate to the territory of Danube Bulgaria. Nowadays the majority of the Bulgarian archaeologists interested in this problem consider that there were no resettlements at all and the connections were sporadic and insignificant. To support this view they argue that no bell kits decorated by lotuses have been found so far. The aim of the paper is to present a rather broad range of finds from Bulgaria which are similar to the objects from the monuments of different variants of the Saltov-Maiaki culture. The material presented by us may be divided into several groups: the objects connected with clothes and toilet articles (fasteners, fibulae, ear sticks, tweezers, hairpins, and mirrors), amulets, pottery, details of belts and horse harness.